Analysis of Breakthrough Reactions in 1,143 Desensitization Procedures in a Single Tertiary Hospital Using a One-Bag Desensitization Protocol - Kim, Hyun Hwa; Seo, Jeongmin; Ahn, Yoon Hae; Kim, Hyunjee; Yoon, Jeong-Eun; Suh, Jang Ho; Kang, Dong Yoon; Lee, Suh Young; Kang, Hye-Ryun (Frontiers in Allergy, 2022)
Background Drug desensitization is helpful for patients who have experienced significant hypersensitivity reactions (HSRs) to antineoplastic agents. One-bag desensitization protocols, attracting attention in recent years, need to be validated on their safety and efficacy in a large number. Methods One-bag desensitization procedures conducted from 2018 to 2020 were analyzed; their outcomes and the risk factors for breakthrough reactions (BTRs) were assessed in desensitization procedures to major drug types (platins, taxanes, and monoclonal antibodies). Results A total of 1,143 procedures of one-bag desensitization were performed in 228 patients with 99% completion rate. BTRs occurred in 26% of the total desensitization procedures—34% in platins, 12% in taxanes, and 18% in mAbs. BTR occurrence rate decreased along the desensitization process with 80% of BTRs occurring within the 6th desensitization attempts. Severe BTR occurred more frequently with severe initial HSRs (1% in mild to moderate initial HSRs vs. 16% in severe). Severe initial HSR was also a significant risk factor for moderate to severe BTR in platins (odds ratio 1.56, 95% confidence interval [CI] 1.06–2.29, p = 0.025). The use of steroid was also associated with lower occurrence of moderate to severe BTR (odds ratio 0.50, 95% CI 0.35–0.72, p < 0.001). Conclusion Most patients with HSRs to antineoplastic agents can safely receive chemotherapy through a one-bag desensitization protocol. Further studies on each drug with larger sample size can help verify the risk factors of BTRs and evaluate the efficacy of steroid premedication in improving the safety of desensitization in high-risk patients.